Research and Application of the Formula for Calculating Discharge Coefficient of the Spillway Broad Crest Weir Based on the Binary Nonlinear Fitting - YAN Zhifang; JIA Yunfei; WANG Yu (Renmin Zhujiang)
In order to facilitate the use of the discharge coefficient table of broad crest weir in the current design code for Spillway of water conservancy,the discharge coefficient formula of broad crest weir is obtained by fitting the data in the current water conservancy code with bivariate rational function approximation.By Comparing the fitting formula with the current power code formula,the results show that the fitting formula is better than the current power code formula.By comparing the error indexes of fitting formula and power code formula,it is found that the error indexes of fitting formula are in the better range under each value of r/H,while the deviation of each error index of power code from the optimal value is small when r/H≥0.20.The fitting formula is used to calculate a series of discharge coefficients corresponding to water head at different fillet radii of a spillway broad crest weir.Through the analysis of the calculation results,it can be seen that the fitting formula can be used to calculate the discharge coefficient of broad crest weir in engineering design instead of consulting the water conservancy code table.